Investigation of GaN with Low Threading Dislocation Density Grown on Graphene/Sputtered AlN Composite Substrate. Issue 8 (8th May 2019) - Zhang, Yachao; Su, Kai; Guo, Rui; Xu, Shengrui; Chen, Dazheng; Zhu, Jiaduo; Bao, Weimin; Zhang, Jincheng; Ning, Jing; Hao, Yue
Abstract : High‐quality GaN film is grown on graphene with the underneath sputtered AlN modified layer using metal organic chemical vapor deposition. Due to the modulation effect of sputtered AlN on the surface potential and the chemical reactivity of graphene, the nucleation probability of GaN is significantly improved. The GaN epitaxial layer shows excellent crystal quality and surface morphology, and has very low threading dislocation density of 1.78 × 10 8 cm −2 . Furthermore, the mechanism of threading dislocation suppression is revealed according to the transmission electron microscope results. The improved nucleation probability and enhanced lateral growth mode lead to the formation of short‐range stacking faults in c ‐plane GaN, which block the propagation of threading dislocations along the growth direction. Moreover, the formation and evolution mechanism of the short‐range stacking faults are discussed. The results in this work not only offer a promising approach to propel the widespread application of GaN on graphene, but also provide a new idea for the regulation and suppression of defects in the growth of nitride semiconductors. Abstract : GaN with low threading dislocation (TD) density is grown on graphene/sputtered AlN composite substrate. The underneath sputtered AlN is beneficial in promoting the surface chemical reactivity of graphene and the nucleation probability of GaN reactive atoms. The enhanced lateral growth mode led to the formation of short‐range stacking faults, which blocked the vertical propagation of TDs and significantly improved the GaN crystal quality.